Quality of Life and Quality of Working Life 2017
DOI: 10.5772/intechopen.69151
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Physical Activity: Their Relationship with Physical and Psychological Well-Being

Abstract: Many studies have been focused on the analysis of diferent factors that relate to the quality of life. And those studies have found a clear relationship between the quality of life, psychological well-being, and health. It is important to know those relationships and to know factors that can improve these three aspects simultaneously. And one of the most important factors is the realization of physical activity on a regular basis. This study analyzes the efect of physical activity on improving the quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…QoL relates to a multitude of aspects such as physical fitness, social environment, education, employment, economic and finance conditions, and other markers such as religion and beliefs, and environment (Katschnig, 1997 ; Coelho et al, 2005 ). Among these elements, physical and mental health play an important role in management and characterization of QoL of a person (Rodríguez-Fernández et al, 2017 ), and especially a patient with cardiac disease (Pedersen et al, 2007 ). In fact, it has been shown that low pre-hospitalization health-related QoL and poor fitness are associated with lower post-hospitalization general health, increased remission rates, and mortality risk (Mendes de Leon et al, 1998 ; Hawkes et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…QoL relates to a multitude of aspects such as physical fitness, social environment, education, employment, economic and finance conditions, and other markers such as religion and beliefs, and environment (Katschnig, 1997 ; Coelho et al, 2005 ). Among these elements, physical and mental health play an important role in management and characterization of QoL of a person (Rodríguez-Fernández et al, 2017 ), and especially a patient with cardiac disease (Pedersen et al, 2007 ). In fact, it has been shown that low pre-hospitalization health-related QoL and poor fitness are associated with lower post-hospitalization general health, increased remission rates, and mortality risk (Mendes de Leon et al, 1998 ; Hawkes et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, many diseases arise due to a sedentary lifestyle. Experts examine physical activity as a preventive effort to improve health and the quality of life (Rodriguez-Fernandez & Zuazagoitia, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The researchers, teachers, and parents should understand the adolescents' view of quality of life, where the adolescents emphasize the importance of social relations and psychosocial health to promote and sustain their quality of life [102]. The data obtained in the research [103] indicate that those who engage in physical sporting activity always have higher psychological well-being levels (p < 0.001), experience more positive emotions (p < 0.001) and fewer negative ones (p < 0.001), and feel more satisfied with their lives (p < 0.001), than those who do not. Linear relationship between greater sport participation and happiness were observed in the results of [104].…”
Section: Discussionmentioning
confidence: 99%
“…Participation in organized sports provides an opportunity for young people to increase their physical activity and develop physical and social skills. And the study of [103] presented the data, which identified that physical activity can be taken as a variable associated with higher well-being scores and the recommended regular basis for exercising should be at least four times a week.…”
Section: Discussionmentioning
confidence: 99%